Electrical measurements on the construction site – an integration between Regulatory Standards 10 and 18 - Lima Neto, Inácio Alves de (Brazilian Journal of Production Engineering, 2024)
Historically, civil construction carries many facts that have contributed to the increase in work accidents; The fuse of the Industrial Revolution, which had put the lives of pregnant women and children at risk with dangerous machinery, long working hours and totally non-existent safety, was a great milestone in occupational safety because, from this milestone, laws and decrees in favor of the worker were created. The regulatory standards of the Ministry of Labor and Employment make a bridge between them, with a view to contributing directly to the risk management process, reducing the exposure of workers to risk agents. From this, the research in question sought, through a documentary study, to establish a direct relationship between NR 18, item 18.6 and NR 10, identifying the electrical risks at the construction site and proposing measures to mitigate them. At the end of the research, it was realized that: in all stages of the work there is an electrical risk and regulatory standards 10 and 18 make a bridge between them to contribute to the risk management process.
Keywords: Occupational Safety; Safety Standards; Risk Management; Civil Construction